2020
DOI: 10.1057/s41271-019-00217-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sugar-sweetened beverage sales volume by sugar content in the United States: implications for tiered taxation and tax revenue

Abstract: This study draws on data on sales volume, brand-level market shares, and sugar content to calculate the distribution of sugar-sweetened beverage (SSB) sales volume by sugar content, propose sugar content thresholds for a tiered tax structure, and estimate tax revenue. The most common SSBs sold had 26 g of sugar/8-oz serving; 70.8% had ≥ 25 g of sugar/8-oz serving, 16.9% were in the 10-15 g range, and 8.7% were in the 16-20 g range. A tiered tax with cut points at < 20 g and < 5 g of sugar/8-oz serving is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…12,14,28 In addition, of key relevance is the fact that sodas are substantial contributors to the volume sold of SSBs 14 and are particularly high-sugar SSBs. 29 This study found that grams of sugar sold from untaxed beverages increased by 4% at year 1 post tax but that this substitution did not persist at year 2 post tax. The change at year 1 post tax stemmed from substitution to sweetened milk, which has not been assessed in previous evaluations.…”
Section: Discussionmentioning
confidence: 67%
“…12,14,28 In addition, of key relevance is the fact that sodas are substantial contributors to the volume sold of SSBs 14 and are particularly high-sugar SSBs. 29 This study found that grams of sugar sold from untaxed beverages increased by 4% at year 1 post tax but that this substitution did not persist at year 2 post tax. The change at year 1 post tax stemmed from substitution to sweetened milk, which has not been assessed in previous evaluations.…”
Section: Discussionmentioning
confidence: 67%
“…below these highly consumed clusters to encourage reformulation. 28 This guidance would imply a threshold of around 8 g/100 mL given the distribution we observed in Barbados, somewhat higher than the threshold used in Chile (6.25 g/100 mL). 43 More empirical work is needed to understand how companies respond to these thresholds in practice and to assess how home-prepared SSBs compare in terms of sugar concentration levels in other settings.…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…Powell et al have assessed the distribution of sugar concentration by consumption of ready-to-drink SSBs (excluding home-prepared SSBs) in the USA and identified two clusters of highly consumed concentration levels. 28 They recommended that SSB tax thresholds should be set at 5 g/8 oz. below these highly consumed clusters to encourage reformulation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 11 Perhaps a better comparison would be to use the same tax level from the tiered tax proposed by Lee et al based on the current distribution of beverage purchases across tiers (1.75 cents per ounce) or the 2 cents-per-ounce tax on the political agenda. 12 Matching the tax level across structures or using a 2 cents-per-ounce volume tax in the Lee et al model would substantially reduce or eliminate the difference in cases of diabetes mellitus and cardiovascular disease averted and the healthcare costs avoided, making the modeled health impacts very similar across the 3 tax structures.…”
mentioning
confidence: 99%
“… 7 A possible unintended consequence of reformulation is the replacement of caloric sweeteners with artificial sweeteners to maintain the same level of sweetness, which is occurring in the United Kingdom 7 and may have negative implications for health, although this evidence is inconclusive. According to a recent study by Powell et al, 12 moving from the highest sugar tier (tier 3) to the middle tier (tier 2) would require a 20% to 38% reduction in sugar content for the vast majority of beverages sold in this category in the United States. The extent to which beverage companies will respond to a tiered tax with this level of reformulation implemented at the local level remains an unanswered question.…”
mentioning
confidence: 99%